(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the expression and specific features of neologisms in translation are studied. Since the first years of independence, Uzbekistan has paid great attention to the education system. Among them, he established relations with foreign countries and began to study their language, culture, and art. New words or neologisms are forged by our creative imagination and reinforced in language through everyday communication.